Welfare effects of a transport subsidy in a spatial price equilibrium - Johannes Bröcker (Technische Universität Dresden, Fakultät Verkehrswissenschaften, 1998)
The paper shows that in a spatial price equilibrium under monopolisitc competition welfare can be increased by subsidising transport. Therefore transport can be said to exert a positive (pecuniary) externality. This is demonstrated by introducing a subsidy into a partial spatial price equilibrium of the Hotelling-Smithies type in one-dimensional space. Two varieties of demand are analysed, linear and negative exponential. The welfare effect of a transport subsidy is shown to be decomposable into three effects, the expansion effect, the competition effect and the market size effect. Numerical results and decompositions are presented.
Keywords: 330; transport; externality; spatial price equilibrium; welfare.